Forecasting future global agricultural water demand: current projections and future challenges - Amarasinghe, Upali A.; Amarnath, Giriraj; Sikka, Alok (Burleigh Dodds Science Publishing Limited, 2024)
Population and economic growth, urbanization, and lifestyle changes are key drivers of water demand estimation. Climatic change and risks add another dimension to the calculus. However, unreliable baseline information and future uncertainties of many drivers are barriers to accurate demand projections, which are essential for future planning. This chapter re-looks at the current global agricultural water demand estimations and challenges for making reliable future projections, which are crucial for two reasons. First is the large share of the water withdrawals and the population that depend on direct and indirect livelihoods at present in the agricultural sector in developing countries. Second, the emerging climatic risks with variable temperatures and rainfall frequently affect agriculture production globally. Because of interlinkages with international trade, accurate global water and food demand productions will be critical for planning food, water, and nutritional security, national climate adaptation actions, and achieving sustainable development targets in many developing countries.